Polyester thin film composite nanofiltration membranes via interfacial polymerization: influence of five synthesis parameters on water permeability - K. H., Mah; Hafizuddin, Wan Yussof; Mazrul Nizam, Abu Seman; A. W., Mohammad (Faculty Mechanical Engineering, UMP, 2018)
Polyester thin film composite nanofiltration membranes were synthesized on the polyethersulfone (PES) support via the interfacial polymerization between triethanolamine (TEOA) and trimesoyl chloride (TMC). Water permeability measurement were conducted on 16 polyester thin film composite membranes to evaluate the influences and interactions of five synthesis parameters: TEOA concentration (X1), TMC concentration (X2), reaction time (X3), pH of aqueous phase solution (X4), and curing (X5). These parameters were varied simultaneously between two limit levels using fractional factorial design, allowing investigation of parameters with lesser samples as well as statistical analysis of results. The regression model between the response and the parameters were developed and the fitted model were tested with analysis of variance (ANOVA). The R2 for the model was 0.94 implying the predicted values were in reasonable agreement with the experimental data, confirming the high predictability of the applied model. The relative size of effects is visually demonstrated in a Pareto chart. It could be concluded that the significant effects were in the order of X2> X5> X2X5> X3> X1. This study leads up to a regression model that will allow the synthesis of polyester thin film composite membranes via interfacial polymerization with desired water permeability within the range studied.